1988
DOI: 10.1677/joe.0.1170139
|View full text |Cite
|
Sign up to set email alerts
|

The stability in vitro of bioactive and immunoreactive LH in human blood and plasma

Abstract: The degree of stability in vitro of bioactive and immunoreactive LH in human blood, plasma and serum was examined. Bioactivity and immunoreactivity of LH were assayed by the dispersed mouse Leydig cell assay and by standard radioimmunoassay respectively, using the same reference preparation (first international reference preparation for human pituitary LH 68/40 for immunoassay). Bioactive and immunoreactive LH were stable in blood and plasma at 22 degrees C for up to 4 and 24 h respectively, and in blood at 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ellis et al (9) reported no statistically significant effects of storage for up to 24 h for FSH and LH, and Evans et al (10) reported no effects for up to 120 days when samples were kept refrigerated. Tsatsoulis et al (15) examined changes in LH when plasma was held at 4jC for up to 24 h in four male subjects and found little variation over time. Key et al (16) analyzed blood samples from 15 women and found increases in testosterone after 6 h of 1.0% (95% CI, À2.5% to 4.5%) in plasma samples and 5.2% (95% CI, 0.2-10.4%) in serum samples, and after 24 h slightly larger changes of 3.2% (95% CI, 1.4-7.9%) in plasma and 6.2% (95% CI, 0.2-12.5%) in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis et al (9) reported no statistically significant effects of storage for up to 24 h for FSH and LH, and Evans et al (10) reported no effects for up to 120 days when samples were kept refrigerated. Tsatsoulis et al (15) examined changes in LH when plasma was held at 4jC for up to 24 h in four male subjects and found little variation over time. Key et al (16) analyzed blood samples from 15 women and found increases in testosterone after 6 h of 1.0% (95% CI, À2.5% to 4.5%) in plasma samples and 5.2% (95% CI, 0.2-10.4%) in serum samples, and after 24 h slightly larger changes of 3.2% (95% CI, 1.4-7.9%) in plasma and 6.2% (95% CI, 0.2-12.5%) in serum.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Both the assays detect intact LH and some fragmented forms probably including the core beta fragment. [41] The quantitative reproducibility of the ICL immunoassay indicates it is more robust for measurements of urinary LH for anti-doping purposes compared with the IF assay. This could explain the consistently lower LH levels measured by the IF assay than the ICL assay.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that plasma LH is stable after storage for 8 and 14 days after refrigeration (4 C), [39,40] for 14 days stored frozen (-6 C) [40] and for up to 9 months after -20 or -70 C storage. [41] The quantitative reproducibility of the ICL immunoassay indicates it is more robust for measurements of urinary LH for anti-doping purposes compared with the IF assay. Nevertheless despite the quantitative reduction in urine LH by the IF assay, the reduction was proportionate over the four years frozen storage.…”
Section: Discussionmentioning
confidence: 99%
“…That these changes are of physiological, and perhaps pathological, relevance is indicated by the substantial number of studies (reviewed recently in Wang, 1988;Wilson et al, 1990;and Tsatsoulis et al, 1991) showing changes in the pattern of gonadotrophin glycoform secretion in different biological situations. The effects of glycosylation on biological activity in vitro appear to be intermediate in importance compared with minor effects on immunoreactivity and the major effects on in-vivo function.…”
Section: Glycosylation Isoforms and Bioactivitymentioning
confidence: 99%
“…(c) The measurement of B : I ratios has been extensively used to characterize the structure-function relationships of LH (reviewed by Dufau and Veldhuis, 1987;Wilson et al, 1990;Tsatsoulis et al, 1991). Such studies need to be carefully evaluated for adequate evidence of parallelism and other tests of biometric validity.…”
Section: Glycosylation Isoforms and Bioactivitymentioning
confidence: 99%